2016
DOI: 10.1080/1547691x.2016.1206998
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to endosulfan induces inflammation in murine colon via β-catenin expression and IL-6 production

Abstract: Endosulfan (ENDO) is a widely used organochlorine (OC) pesticide and persistent organo-pollutant. Epidemiological studies have shown that high levels of OC exposure were related to colorectal cancer (CRC) incidence. The objectives of the present study were to evaluate histological changes in the colon, as well as in in situ expression of b-catenin and P-selectin, and serum levels of select pro-inflammatory cytokines in mice administered ENDO; there is a relationship between increased serum IL-6 and P-selectin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Exposure to endosulfans and dieldrin can increase the expression levels of the pro-in ammatory factors IL-6, IL-8, IL-1β, and TNF-α, as evidenced in molecular studies [13,46]. Female mice and rats had increased levels of pro-in ammatory cytokines when exposed to doses ranging from 2-50 mg/kg of endosulfans [18,47], which is consistent with our results. However, no signi cant associations were found between serum dieldrin, endosulfan-α, and endosulfan-β and cytokines (i.e., IL-2, IL-4, IL-6, and IL-10) in preterm birth cases in a case-control study in India, and only endosulfan-β was positively correlated with IL-2 in the controls [48].…”
Section: Discussionsupporting
confidence: 90%
“…Exposure to endosulfans and dieldrin can increase the expression levels of the pro-in ammatory factors IL-6, IL-8, IL-1β, and TNF-α, as evidenced in molecular studies [13,46]. Female mice and rats had increased levels of pro-in ammatory cytokines when exposed to doses ranging from 2-50 mg/kg of endosulfans [18,47], which is consistent with our results. However, no signi cant associations were found between serum dieldrin, endosulfan-α, and endosulfan-β and cytokines (i.e., IL-2, IL-4, IL-6, and IL-10) in preterm birth cases in a case-control study in India, and only endosulfan-β was positively correlated with IL-2 in the controls [48].…”
Section: Discussionsupporting
confidence: 90%
“…In vivo studies have shown that endosulfan exposure can increase the level or activity of a number of inflammatory factors in animals. For example, inducible nitric oxide synthase was elevated by endosulfan exposure in rat and frog tissues [ [12] , [24] , [25] ], and increased expression of inflammatory cytokines, including TNF, IL-1 and IL-6, have been reported in rats and mice [ [26] , [27] , [28] ]. In many tissues, macrophages are a principle source of inflammatory cytokines and NO.…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with the tendency of fish intestine to present a wider lamina propria. The effects of certain contaminants on gut cytokines have been described in mammals, with an increase in proinflammatory cytokines, including il-6 or tnf-α associated with CPF exposure (Li et al, 2019) or organochlorine pesticides (Téllez-Bañuelos et al, 2016). Conversely, virgin MPs and chemical pollutants used singularly did not induce the expression of tested immunity-related cytokines.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%